2008
DOI: 10.1086/526416
|View full text |Cite
|
Sign up to set email alerts
|

Remote Sensing of Gamma‐Ray Emission from Solar Energetic Proton Interactions with the Solar Wind

Abstract: The properties of solar energetic particles (SEPs) in solar flares are studied through remote imaging in the radio, hard X-ray, and -ray energy ranges. However, the heliospheric SEP populations are observed only in situ by satellite measurements, which drastically limits our understanding of their spatial and temporal variations. Can those SEP populations be remotely imaged, as are the solar SEPs? We consider two possibilities for detecting faint -ray emission from SEP interactions with solar wind (SW) ions. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…If that were the case, the ions might be expected to interact with ambient material in a more diffuse pattern, perhaps at some distance from the flare. This shows that the γ-ray emission does not result from the interaction of solar energetic particles with the solar wind as alternatively proposed by Kahler & Ragot (2008).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…If that were the case, the ions might be expected to interact with ambient material in a more diffuse pattern, perhaps at some distance from the flare. This shows that the γ-ray emission does not result from the interaction of solar energetic particles with the solar wind as alternatively proposed by Kahler & Ragot (2008).…”
Section: Discussionsupporting
confidence: 73%
“…Also, it has not confirmed the SMMera suggestion that 2.223 MeV line emission might be produced over an extended region (Vestrand & Forrest 1993). The observations are also not consistent with a production of γ-rays through the interaction of solar energetic protons with the solar wind as examined by Kahler & Ragot (2008). We may look forward to further advances, both observational (e.g., with GRIPS; Shih et al 2009a), and theoretical, over the next few years.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 83%
“…Various mechanisms exist (e.g. Moskalenko et al 2006;Kahler & Ragot 2008), and both EGRET (Orlando & Strong 2008) asyet-unpublished Fermi results show a distinct source of high-energy γ rays from the solar direction. The particle environment of the corona itself may play a role in understanding this source and its relationship to solar-system background sources for Fermi observations.…”
Section: Discussionmentioning
confidence: 99%
“…The first investigation considered gamma-ray emission from high energy (E > 300 MeV) ion collisions with solar wind ions. This research effort found that such emission might be detected for very energetic SEP events [4,5]. Furthermore, a description of aSEP short-term warning model and its performance in preliminary evaluation was completed.…”
Section: Solar Energetic Particle (Sep) Forecast Modelmentioning
confidence: 99%